Survival and growth responses of snakehead fish Channa striata Bloch. juvenile in aerated and unaerated acid sulfate water - , Purnamawati; Daniel Djokosetiyanto; Kukuh Nirmala; Enang Harris Surawidjaja; Ridwan Affandi (Jurnal Akuakultur Indonesia)
ABSTRACT